The uses of referral Clauses in Positive Law - Celis Vela, Dúber Armando (EUNOMÍA. Revista en Cultura de la Legalidad, 2025)
In a legal system, it is common to find provisions that refer to other normative bodies. These references are far from being univocal, as they are not limited to establishing a supplementary regime to facilitate the integration of the law in specific cases. This article aims to analyze the uses of a referral clause in the legislation and, additionally, to evaluate the theoretical-dogmatic problems it creates in determining the content of current law. The methodology applied is rational reconstruction and a critical review of the referral technique as a model for regulating conduct. The text proposes a taxonomy of these norms and examines their implications in identifying the law.
Keywords: Referral clauses; normative integration; legal system; systematization of norms; legislative openness; legislative reserve